Relevance and Implementation of Rural Funding Allocation in West Pasaman after the Implementation of Law Desa - Novi Zulfikar; Afriva Khaidir; Helmi Hasan; Hidayani Syam (Jurnal Aplikasi IPTEK Indonesia, 2019)
The issuance of law no. 6 year 2014 on Desa reinforces the rural authority on managing its financial affairs leading to rural autonomy. However, since the implementation of ADD dan ADN in West Pasaman Regency, some issues have still been identified. This research aims to find out the relevance and implementation of ADD funding allocation in West Pasaman regency after the law no. 6 year 2014 on Desa. This research uses qualitative approach with the key informants of all wali nagari (village heads) in West Pasaman selected by using snowball sampling technique. Data were collected through documentation, interview, and observation. The findings of the research reveal that planning and fund allocating of ADD in nagari (rural area) of West Pasaman have generally run properly. The implementation of ADD is implemented well. The relevance of rural funding allocation with regent’s policy No. 122 year 2016 in Pasaman has been achieved. However, the problem is still found in the implementation of ceiling fund.